Influence of radiation-induced defects on CdTe and CdZnTe detectors properties - Kondrik, A.I. (Вопросы атомной науки и техники, 2015)
The correlation between radiation-induced defects, arising in CdTe:Cl and CdZnTe after the hard X-ray irradiation, and charges collection efficiency of detectors based on these materials has been investigated by means of computer simulation method. The role of radiation-induced defects during degradation of CdTe:Cl detector performance has been determined. An attempt to explain the reasons for higher radiation resistance of CdZnTe compared with CdTe:Cl has been made.